Benefits of perioperative sildenafil therapy in children with a ventricular septal defect with pulmonary artery hypertension on early surgical outcomes. Issue 12 (16th September 2020) - Patel, Ruchit; Thingnam, Shyam Kumar Singh; Mishra, Anand Kumar; Rohit, Manoj Kumar; Upadhyay, Vinay; Halder, Vikram; Bansal, Vidur
Abstract: Objectives: Pulmonary hypertension is a common association in children with nonrestrictive ventricular septal defect. It increases perioperative mortality and morbidity. Oral sildenafil is an effective pulmonary vasodilator. In this study, we assessed effects of perioperative oral sildenafil therapy on pulmonary artery pressure and early surgical outcomes. Methods: This was a single centre, prospective randomized control study. Thirty children with nonrestrictive ventricular septal defects with pulmonary hypertension were divided into two groups. In the sildenafil group ( n = 15, mean age 23.3 months), oral sildenafil was administered two weeks before surgery. In the control group ( n = 15, mean age 36 months), preoperative sildenafil was not given. Sildenafil was continued postoperatively in both groups, provided the postoperative pulmonary artery pressure was over 50% of systemic pressure. Results: There was no perioperative mortality, pulmonary hypertensive crisis and there were no intolerable side effects related to sildenafil in either group. Mean pulmonary artery pressure showed a reduction in both groups. Sildenafil group showed statistically significant improvement in duration of cardiopulmonary bypass (100.27 ± 21.09 min vs. 125.40 ± 26.83 min, p = .008), mechanical ventilation requirement (22.79 ± 17.13 h vs. 30.53 ± 13.05 h; p = .04), epinephrine requirement (22% patients vs. 48% patients; p = .03) and hospital stay (6.13 ± 1.40 days vs. 7.53 ± 1.92 days; p = .05). Conclusion: Oral Sildenafil therapy is an inexpensive and well‐tolerated method for reducing pulmonary hypertension secondary to non‐restrictive ventricular septal defect. It has noteworthy advantages regarding early surgical outcomes like reduced cardiopulmonary bypass time, improved mechanical ventilation time, lower inotrope requirement and shorter hospital stay if used preoperatively in select patient population.